2016 ASAHP Annual Conference: Abstracts of the Presentations…Clinical Remuneration: A Standardized Model for Affiliate-Based Health Science Programs. - Anderson, Roy B. (Journal of Allied Health)
Historically, Cleveland Clinic Health System hospitals received clinical remuneration for providing clinical experiences for students in nine health science disciplines from seven academic institutions. In 2008-2009 as Cleveland Clinic regional hospital legal offices were integrated into one department, a system-wide affiliation agreement template was created. In consolidating the agreements to the new template, existing program clinical remuneration rates were found to be inconsistent between health science programs, academic institutions and Cleveland Clinic hospitals. It was also discovered that although local health science programs were paying clinical remuneration, some out-of state counterparts were not. Published references of academic programs paying hospitals and healthcare agencies for training health science students date back to the late 70s and 80s; however, no published references could be found suggesting the possible use of a clinical remuneration model or formula for all health science programs. This presentation will discuss the process used by Cleveland Clinic to engage the academic institutions in reviewing clinical education outcomes and clinical contact hours of three health science disciplines; a percent effort study of Cleveland Clinic health science preceptors; and the development of an equitable clinical remuneration model that was approved by Cleveland Clinic executive leadership for implementation in Fall 2016.